PERAN GURU PAUD DALAM MENANAMKAN MORAL SEBAGAI FONDASI PENDIDIKAN KEWARGANEGARAAN SEJAK DINI - Sofiyati, Ely; Syakiro, Imma; Malik, Lina Revilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Instilling moral values from an early age is an important foundation in civic education to shape the character and personality of children as future citizens. Technological developments and the dynamics of children as future citizens. Technological developments and social dynamics in the digital age have also given rise to challenges in the form of moral degradation that need to be anticipated through education from an early age. This study aims to describe the role of early childhood teachers in instilling moral values as the foundation of early civic education, as well as to examine the learning strategies used in the process. This study uses a literature review method by analyzing various scientific sources in the form of journal articles, books, and academic publications relevant to moral education, civic education, and early childhood education. Data analysis techniques were carried out using content analysis to identify themes, patterns, and key findings from the literature reviewed. The results of the study show that PAUD teachers have a very important role as moral role models, designers of value-based learning, and facilitators of meaningful play activities. This study confirms that strengthening the role of PAUD teachers and applying appropriate learning strategies are the main keys to instilling moral values as the foundation of civic education from an early age.